BENEFITS OF OAT MILK - Aminova Mohirakhon Mo'minjon qizi; Nazirova Rahnamokhon Mukhtorovna (TADQIQOTLAR, 2025)
Annotation:This  article  explores  the  growing  popularity  and  diverse  health, environmental, and practical benefits of oat milk as a leading plant-based alternative to traditional dairy. It examines its nutritional profile, focusing on its high fiber content (particularly beta-glucans), low saturated fat, and absence of lactose, which make it a favorable choice for individuals with dietary restrictions, including lactose intolerance and nut allergies. Furthermore, the article discusses the sustainability advantages of oat milk production compared to dairy and other plant-based milks, analyzing its lower water and land usage. The paper concludes by evaluating its culinary versatility and market  acceptance,  solidifying  its  position  as  a  significant  component  of  modern, health-conscious diets.